GENDER-BASED SPEAKING ANXIETY IN ONLINE ENGLISH AS FOREIGN LANGUAGE POSTGRADUATE STUDENTS - Majid, Rusni Hi.; Amri, Misbahul; Zen, Evynurul Laily (Universitas Muhammadiyah Metro, 2025)
Speaking anxiety became one of the common problems faced by EFL students at any level. This study aims to determine the speaking anxiety level among postgraduate EFL students as well as the contributing factors to speaking anxiety in the setting of online learning. The data were collected from 20 respondents through a questionnaire adapted from Horwitz. The respondents are postgraduate EFL students from the 2023 batch at one of the universities in Malang. The survey was chosen to collect the data. The questionnaire was distributed through WhatsApp. In analyzing the data, the researcher used SPSS-24. The finding revealed that male students have moderate speaking anxiety, and the dominant factors causing it were fear of communication, next comes test anxiety, and fear of negative evaluation. In contrast, female students have significant levels of speaking anxiety. Variables contributing to their speaking anxiety involve fear of negative evaluation. The next one is anxiety in communication and test anxiety. Because of that, it can be stated that female students have a higher level of anxiety compared to male students. The results can help educators in teaching online learning to understand students' anxiety based on their gender.